The impact of MSPO towards environment among workers in SPPK / Nik Nurlaila Akma Nik Muhamad and Syahrizan Syahlan - Nik Muhamad, Nik Nurlaila Akma; Syahlan, Syahrizan (Faculty of Plantation and Agrotechnology, 2018)
In Malaysia, oil palm is the most crop that are planted in the field because the demand of palm oil is rising from year to year. Improper good management practices for opening new area and managing the field for oil palm plantation purpose give huge impact on environment. To ensure the sustainability of oil palm in Malaysia. Malaysia Standard Palm Oil (MSPO) standard was launched on 2013 for sustaining oil palm plantation without harming the planet and people. By the end of the year 2019, MSPO standard has been mandatory for all growers. The purpose of this study is to identify' the factors and relationship between impact of MSPO and environment. This study consists of training, knowledge and estate support as independent variables. This study is conducted at Syarikat Perladangan Peserta Kundang Ulu Tangkak. Johor and from 62 populations. 52 samples randomly selected to answer the questionnaire survey as respondents. All the variables are positive relationship but the strongest relationship toward dependent variable are training and knowledge. The results showed the value of R2 was 0.247 which indicate 25% of independent variable have been identified in this study and the rest are not included in this study. Hence, it can conclude that, the most dominant and significant factors that impact on environment are training and knowledge. Meanwhile, estate support is not significant factor that impact on environment because workers are lack received support from the estate.